Aplikasi Uji Wilcoxon Signed Rank untuk Menganalisis Pengaruh COVID-19 pada Prestasi Belajar - Afifah, Ngizatul; Setiawani, Susi; Prihandini, Rafiantika Megahnia; Angrenani, Arin Berliana; Putri, Inge Wiliandani Setya; Salim, Abdurrahman (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2025)
Education in Indonesia faced significant challenges during the COVID-19 pandemic, particularly with the transition from face-to-face to online learning. Many obstacles occur in this online learning system which may affect student achievement. This research aims to analyze the effect of the COVID-19 pandemic on student achievement which is reviewed statistically descriptively and inferentially. This research was conducted at SMK Ma'arif 9 Kebumen with a sample of one class X. The research method used was using a quantitative approach, namely the Wilcoxon Signed Rank Test. The analysis results show that based on a 95% confidence level, there is a significant difference between the average learning achievement of students before the pandemic and after the COVID-19 pandemic occurred, with a decrease in the average student scores of 2.98% from the average student scores before the COVID-19 pandemic. Keywords: Wilcoxon Signed Rank Test, COVID-19's Impact, Learning Achievement